Odpowiedzi

2009-12-04T00:08:10+01:00
A)
s=(a+b+c)/3 |*3
3s=a+b+c |-a-b
c=3s-a-b

c)
R=U/I |*I
RI=U |÷R
I=U/R

d)
V=⅓Pph |*3
3V=Pph |÷h
Pp=3V/h

e)
E=½mv² |*2
2E=mv² |÷v²
m=2E/v²

f)
Cp=Ms*100%/Mr |*Mr
Cp*Mr=Ms*100% |÷Cp
Mr=Ms*100%/Cp
2009-12-04T00:24:24+01:00
A)
s = ⅓ (a + b + c) |* 3
3s = a + b + c
a + b + c = 3s
c = 3s - a - b

c)
R = U / I |*I
R * I = U |: R
I = U/R

d)
V = ⅓ Pp * h |* 3
3V = Pp * h |:h
Pp = 3V / h

e)
E = ½ m * v² |*2
2E = m * v² |: v²
m = 2E / v²

f)
Cp = (Ms * 100%) / Mr |*Mr
Cp * Mr = Ms * 100% |:Cp
Mr = (Ms * 100%) / Cp